The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/agj2.21041
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine, mesosulfuron‐methyl, and topramezone persistence in North Carolina soils

Abstract: Investigating the effects of soil properties on herbicide persistence can aid in evaluating the carryover potential of herbicides in soil and the consequent injury risk to rotational crops. Laboratory incubation experiments were conducted to quantify the persistence of atrazine, mesosulfuron-methyl, and topramezone in five regional soils under aerobic conditions at 23 ˚C. Additionally, mesosulfuron-methyl persistence was tested at 7 ˚C, which is representative of regional average winter soil temperature. Herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In the selected soil types, estimated mesosulfuron‐methyl concentrations for 30%, 50%, or 80% visual injury or aboveground dry biomass reduction in soybean and canola at all evaluation timings always exceeded the predicted average carryover concentration of 0.06 g ai ha −1 (Table 5). This concentration was calculated from linear regression equations describing mesosulfuron‐methyl persistence in the selected soil types in a previous study (Ramanathan et al., 2022). However, Grey and McCullough (2012) found that carryover residue from chlorsulfuron and metsulfuron‐methyl when applied in combination at rates of 88.0 and 18.0 g ai ha −1 , respectively, caused significant height reduction in soybean, and height and yield reduction in cotton.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the selected soil types, estimated mesosulfuron‐methyl concentrations for 30%, 50%, or 80% visual injury or aboveground dry biomass reduction in soybean and canola at all evaluation timings always exceeded the predicted average carryover concentration of 0.06 g ai ha −1 (Table 5). This concentration was calculated from linear regression equations describing mesosulfuron‐methyl persistence in the selected soil types in a previous study (Ramanathan et al., 2022). However, Grey and McCullough (2012) found that carryover residue from chlorsulfuron and metsulfuron‐methyl when applied in combination at rates of 88.0 and 18.0 g ai ha −1 , respectively, caused significant height reduction in soybean, and height and yield reduction in cotton.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of this research was to evaluate herbicide carryover injury risk in varying soils based on differences in herbicide bioavailability. Of the regional soils in which atrazine, mesosulfuron-methyl, and topramezone persistence were quantified in previous research by Ramanathan et al (2022), Candor sand, Creedmoor sandy loam, and Portsmouth sandy loam were selected as soils of interest for the present study owing to the range in herbicide half-life among these soil types and their varying textural and physicochemical properties. Bioassays are powerful tools by which measurements of such plant responses to herbicides can be used to evaluate soil-herbicide-plant relationships (Jeffries & Gannon, 2016;Loux, 1990;Sandín-España et al, 2011;Strebig & Kudsk, 1993).…”
Section: Core Ideasmentioning
confidence: 99%
See 3 more Smart Citations